Enhancing school communities via program 'Dr to Be' and 'Scientist to Be': a case study of a private islamic tahfiz school in Penang, in collaboration with Universiti Teknologi MARA, Universitas Airlangga and Universitas Muhamadiyah Malang, Indonesia - Ismail, Wan Ismahanisa (Universiti Teknologi Mara, Kedah, 2024)
This study explores the implementation and impact of the "Dr to Be" and "Scientist to Be" programs at a private Islamic tahfiz school in Penang, Malaysia. In collaboration with Universitas Airlangga (UNAIR) and Universitas Muhamdiyah Malang(UMM) in Indonesia, these programs aim to inspire and educate students about careers in medicine and science start from primary to secondary school. Through a series of structured activities including talks, hands-on medical workshops, shadowing opportunities, and mentorship initiatives between University students and school students. The programs seek to engage students in practical learning experiences. The case study examines the strategies employed to integrate these programs into the school curriculum, highlighting the involvement of external experts and educators from Universitas Airlangga and Universiti Teknologi MARA(UiTM). It explores the outcomes of these initiatives, including increased student interest in pursuing careers in medicine and science, enhanced educational outcomes, and strengthened community partnerships between the school and the university. By fostering a supportive learning environment and providing exposure to real-world applications of medical and scientific principles, the programs aim to empower school communities, equip students with essential skills, and cultivate a passion for lifelong learning and professional development in the fields of medicine and science.